2018
DOI: 10.1007/s11606-018-4436-4
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the 2015 US Preventive Services Task Force Screening Criteria for Prediabetes and Undiagnosed Diabetes

Abstract: Diabetes screening that follows the limited USPSTF criteria will identify approximately half of US adults with dysglycemia. Screening other high-risk subgroups defined in the USPSTF recommendation would improve detection of dysglycemia and may reduce associated racial/ethnic disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Further, in a similar investigation, 66% of respondents met the American Diabetes Association's diabetes screening criteria; however, only 46.2% reported receiving any form of screening such that 3.7% were classified as having undiagnosed type 2 diabetes and 36.3% were classified as having undiagnosed prediabetes [29]. O'Brien et al [30] revealed only half of American adults with dysglycemia would be identified following USPSTF screening criteria and that more rigorous diabetes risk factors should be included in screening efforts to promote early detection and intervention in high-risk groups.…”
Section: Discussionmentioning
confidence: 92%
“…Further, in a similar investigation, 66% of respondents met the American Diabetes Association's diabetes screening criteria; however, only 46.2% reported receiving any form of screening such that 3.7% were classified as having undiagnosed type 2 diabetes and 36.3% were classified as having undiagnosed prediabetes [29]. O'Brien et al [30] revealed only half of American adults with dysglycemia would be identified following USPSTF screening criteria and that more rigorous diabetes risk factors should be included in screening efforts to promote early detection and intervention in high-risk groups.…”
Section: Discussionmentioning
confidence: 92%
“…This is consistent with the study by O’Brien, et al, which found a positive predictive value for the USPSTF limited criteria of 62% (95% CI 57.8-66.1). 7 This suggests that the high rate of diabetes and prediabetes is not due to clinicians selecting high risk patients for screening, but rather is the true prevalence in the population and clinicians are potentially missing diagnoses for patients who were eligible but not screened. In addition, clinicians missed the diagnoses for 7363 patients, 32.9% of those who were screened.…”
Section: Discussionmentioning
confidence: 99%
“…3 Screening based on this criteria has been found to have a sensitivity of 47.3% and a specificity of 71.4%. 7 This study excluded those with previously diagnosed diabetes or who were pregnant during the study period. Participants with a history of prediabetes were included if they met criteria for diabetes screening.…”
Section: Methodsmentioning
confidence: 99%
“…The United States Preventive Services Task Force (USPSTF) recommends screening for abnormal blood glucose in adults aged 40–70 years with overweight or obesity [12]. A study of the performance of the USPSTF recommendations revealed that only half of the individuals with undiagnosed dysglycaemia were detected, and substantially less in racial/ethnic minorities [13]. The Canadian primary care system, which screens its patients as early as 40 years of age, found that useful in detecting unrecognised diabetes.…”
Section: Screeningmentioning
confidence: 99%